Graphene-triphenyl phosphate (TPP) co-exposure in the marine environment: Interference with metabolism and immune regulation in mussel Mytilus galloprovincialis - Fei Li (Elsevier, 2021)
Both immune regulation and endocrine systems are great challenges to marine organisms, and effective protocols for determining these adverse outcome pathways are limited, especially in vivo. The increasing usage of graphene nanomaterials can lead to the frequent exposure to marine organisms. Triphenyl phosphate (TPP), an organophosphate flame retardant, is frequently detected in natural environments. In this study, the combined toxic effects of co-exposure to graphene and TPP was investigated in Mytilus galloprovincialis using computational toxicology and multi-omics technology. Noticeably, graphene could disturb the membrane stability and increase the tissue accumulation of TPP. The adsorption behavior of TPP on graphene could inhibit the surface activity of graphene. In the digestive gland, transcriptomics analysis revealed the down-regulated genes in graphene + TPP treatment, including glyceraldehyde-3-phosphate dehydrogenase (GAPDH), sorbitol dehydrogenase (SORD), glutathione s-transferase mu 3 (GSTM3) and 4-aminobutyrate aminotransferase (ABAT), were mainly associated with oxidative stress and energy metabolism. Moreover, metabolic responses indicated that graphene + TPP could cause disturbances in energy metabolism and osmotic regulation marked by differentially altered ATP, glucose and taurine in mussels. These data underline the need for further knowledge on the potential interactions of nanomaterials with existing contaminants in marine organisms.